497 Patient perspectives of safe and routine deprescribing for older people living with polypharmacy: an interview study. (13th April 2023) - Okeowo, D A; Fylan, B; Zaidi, S T R; Alldred, D P
Abstract: Introduction: Stopping medicines where harms outweigh benefits (deprescribing) (1) can reduce adverse events from inappropriate polypharmacy. Deprescribing should be undertaken in a patient-centred way with shared decision-making. However, there is a lack of evidence about the patient perspective on how deprescribing should be safely and routinely implemented in UK primary care. Such evidence is needed to enhance the implementation of deprescribing in primary care. Aim: To identify optimal methods of introducing and actioning deprescribing from the patient's perspective To understand the nature of support patients require during deprescribing To identify patient views on the involvement of different healthcare professionals in deprescribing. Methods: UK patients aged ≥65 years taking ≥5 medicines and living in their own homes were recruited through social media, service user groups and NIHR People in Research. An interview guide was developed using deprescribing literature, patient and public involvement input, and informed by the theoretical implementation framework Normalisation Process Theory (2). Interviews were conducted online (Microsoft Teams®) or via telephone, audio recorded and transcribed verbatim. Data were analysed using the Framework method. Results: Twenty patients, diverse in age and gender, were recruited and three main themes developed: 1. 'Why deprescribe now?' focused on the importance of communicating the deprescribing rationale; 2. 'Monitoring and follow-up' in which safety netting around deprescribing and patients' motivations to self-monitor after deprescribing interventions were highlighted; 3. 'Roles and relationships' focused on patient views of different healthcare professionals involved in deprescribing and the interpersonal skills needed to develop therapeutic relationships. Conclusion: Optimal methods of introducing deprescribing from the patient's perspective included communication of a convincing and well-communicated rationale for stopping medicines. Patients required support from a range of healthcare professionals with whom they had an existing therapeutic relationship. Whilst patients were motivated to self-monitor any unwanted/unexpected effects post-deprescribing, this was under the condition that timely support would be available when needed. These findings provide a deeper understanding of patients' needs for the implementation of safe and routine deprescribing in primary care, and these should be considered when designing medication review and deprescribing services. A strength of this study was the overall diversity in age and gender of the patients interviewed. However, although multiple recruitment pathways were utilised, due to the COVID-19 pandemic, recruitment was mainly online which will have excluded patients who did not have access to the internet. References: 1. Scott, I. A., Hilmer, S. N., Reeve, E., Potter, K., Le Couteur, D., Rigby, D., Gnjidic, D., Del Mar, C. B., Roughead, E. E., Page, A., Jansen, J. & Martin, J. H. 2015. Reducing Inappropriate Polypharmacy: The Process of Deprescribing. JAMA Internal Medicine 175, 827-834. 2. Murray, E., Treweek, S., Pope, C., Macfarlane, A., Ballini, L., Dowrick, C., Finch, T., Kennedy, A., Mair, F., O'donnell, C., Ong, B. N., Rapley, T., Rogers, A. & May, C. 2010. Normalisation process theory: a framework for developing, evaluating and implementing complex interventions. BMC Medicine 8, 63.